2021
DOI: 10.37362/jlb.v5i1.571
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Online Gaming Addiction On Behavior Change Among Adolescents

Abstract: Online game addiction is a bad habit that can damage the health of ourselves and others, dependence on online games will attack our vision if overused and can also affect our behavior. This habit does not only occur in adults but has spread to adolescents and even elementary school students. The purpose of this study is to know online game addiction to behavior change among adolescents at SMPN 1 Bulukumba in 2020. This research uses quantitative methods. The research subjects were 32 respondents who were selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…The results of this study revealed that game addiction affects various aspects of a person's anxiety, be it physical, psychological, social, or academic. The same results were also found in previous studies that gaming addiction can cause psychological problems such as loneliness and anxiety if not playing [9], [10], [16], physical problems such as frequent dizziness, fatigue, musculoskeletal problems, to sleep disorders [7], [17], social problems such as conflicts with parents, close people, to not have friends in the real world [5], [7], [17], and academic problems such as failure in college, not focusing on studying, and not attending [4], [17]. Gaming addiction is detrimental to college students physically and psychologically, and academically.…”
Section: Discussionsupporting
confidence: 89%
“…The results of this study revealed that game addiction affects various aspects of a person's anxiety, be it physical, psychological, social, or academic. The same results were also found in previous studies that gaming addiction can cause psychological problems such as loneliness and anxiety if not playing [9], [10], [16], physical problems such as frequent dizziness, fatigue, musculoskeletal problems, to sleep disorders [7], [17], social problems such as conflicts with parents, close people, to not have friends in the real world [5], [7], [17], and academic problems such as failure in college, not focusing on studying, and not attending [4], [17]. Gaming addiction is detrimental to college students physically and psychologically, and academically.…”
Section: Discussionsupporting
confidence: 89%